2008
DOI: 10.1161/atvbaha.108.165084
|View full text |Cite
|
Sign up to set email alerts
|

Acute Elevation of Plasma PLTP Activity Strongly Increases Pre-existing Atherosclerosis

Abstract: Objective-A transgenic mouse model was generated that allows conditional expression of human PLTP, based on the tetracycline-responsive gene system, to study the effects of an acute increase in plasma PLTP activity as may occur in inflammation. Methods and Results-The effects of an acute elevation of plasma PLTP activity on the metabolism of apolipoprotein B-containing lipoproteins and on diet-induced pre-existing atherosclerosis were determined in mice displaying a humanized lipoprotein profile (low-density l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…In genetically engineered mice, contradictory observations were reported with either no change, a PLTP-mediated increase, or a PLTP-mediated decrease in HDL particle size. 27,[35][36][37][38][39] In contrast, the present rabbit data resemble some human observations in which increased PLTP activity was associated with enlarged HDL. 17,40 It is likely to result from the previously described conversion process involving the fusion of HDL particles of intermediate size.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…In genetically engineered mice, contradictory observations were reported with either no change, a PLTP-mediated increase, or a PLTP-mediated decrease in HDL particle size. 27,[35][36][37][38][39] In contrast, the present rabbit data resemble some human observations in which increased PLTP activity was associated with enlarged HDL. 17,40 It is likely to result from the previously described conversion process involving the fusion of HDL particles of intermediate size.…”
supporting
confidence: 78%
“…Two main points should be considered when addressing the putative molecular mechanism that would account for the more severe hypercholesterolemic trait of cholesterol-fed HuPLTPTg rabbits as compared with cholesterol-fed WT rabbits. First, when PLTP was found to delay the catabolism of apoB-containing lipoproteins in some of the earlier mouse studies, it was accompanied by both the accumulation of triglyceride-rich lipoproteins in plasma 35 and marked alterations in LDL structure and composition. 42 It was not the case in the present study after 8 weeks of dietary manipulation because in cholesterol-fed HuPLTPTg rabbits the plasma triglyceride concentration, as well as the overall structure and composition of circulating apoB-containing particles, remained unchanged despite a 50% increment in LDL particle number as compared with cholesterol-fed WT rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…This results in an atherogenic lipoprotein profile with elevated VLDL and reduced HDL, increased plasma cholesterol, and impaired reverse cholesterol transport. Accordingly, hypercholesterolemic mice carrying a PLTP transgene develop accelerated atherosclerosis (36,37), whereas PLTP deficiency protects from disease (38).…”
Section: Discussionmentioning
confidence: 99%
“…In apoB-transgenic and apoE-deficient mice, PLTP deficiency markedly decreased atherosclerosis. 11 This concept was supported by results of PLTP over-expression in mice lacking either apoE 12, 13 or the LDL receptor, 14 in which over-expression of PLTP increased atherosclerosis. However, a study has suggested that expression of PLTP in macrophages is atheroprotective in LDLR-deficient mice with systemic PLTP deficiency.…”
Section: Introductionmentioning
confidence: 92%